VARIASI MORFOLOGI SISIK PADA IKAN FAMILI CYNOGLOSSIDAE: SEBUAH TINJAUAN LITERATUR - Suchy Rahmadhani; Abdul Razak (Universitas Cokroaminoto Palopo, 2026)
The tonguefish (family Cynoglossidae) is characterized by its flattened body and is widely distributed across the Indo-Pacific, India, Pakistan, and the Red Sea. This study aims to analyze the variation of scale types in the family Cynoglossidae based on a literature review. The literature search was conducted using electronic databases, namely Google Scholar, PubMed, and ScienceDirect. The keywords used in the search were